2001
DOI: 10.1001/archderm.137.11.1437
|View full text |Cite
|
Sign up to set email alerts
|

Trichorhinophalangeal Syndrome Type I

Abstract: Background: Trichorhinophalangeal syndrome type I (TRPS I) is a rare autosomal dominant disorder clinically characterized by sparse and slow-growing hair, pearshaped nose, elongated philtrum, thin upper lip, and bone deformities, in particular, cone-shaped epiphyses of the phalanges. Very recently, the responsible gene TRPS1 has been cloned on human chromosome 8q24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…[114] Changes in the nails were described as thin and fragile nails. Additional changes included shortening and broadening of nails giving rise to the appearance of racket nails[15] which correlates to our case. The most interesting intra-oral finding in the presented case was three impacted and seven completely erupted supernumerary teeth which pose an important clinical significance for the dentists.…”
Section: Discussionsupporting
confidence: 74%
“…[114] Changes in the nails were described as thin and fragile nails. Additional changes included shortening and broadening of nails giving rise to the appearance of racket nails[15] which correlates to our case. The most interesting intra-oral finding in the presented case was three impacted and seven completely erupted supernumerary teeth which pose an important clinical significance for the dentists.…”
Section: Discussionsupporting
confidence: 74%
“…Interestingly, the patient showed a unique pattern of scalp hair loss, manifesting as triangular loss of hair in the mid occipital scalp, which was previously described in this syndrome[7] and might have been overlooked in additional patients. Our patient was diagnosed in a relatively advanced age, suggesting that the prevalence of TRPS type I is probably still underestimated and should be considered by dermatologists when examining new patients.…”
Section: Discussionmentioning
confidence: 70%
“…In our family, however, there was no evident intrafamilial clinical variability; growth delay ranged between ≥ 2.5 and ≥ 3 SD and severe brachydactyly in hands and feet was evident in all family members. Additional associated physical signs reported in TRPS type I, such as endocrine disturbance was not present in either of our family members [8, 25–27] In 2000, Momeni et al reported TRPS1 as the causal gene of TRPS [5]. This gene maps to 8q23.3 and encodes for a 141 kD multi zinc-finger transcription factor protein composed of 1294 amino acids with 9 putative zinc-finger motifs.…”
Section: Discussionmentioning
confidence: 72%
“…Thus TRPS1 haploinsufficiency impairs endochondral cartilage differentiation and epithelial cell interactions in developing hair follicles by altering many signaling pathways as STAT3 and WNT/β catenin [7, 2830]. Many studies reported mutations in the TRPS1 gene and to date it appears to be the only gene associated with the TRPS phenotype [6, 8, 9, 27, 28]. According to the Human Genome Mutation Database, more than 120 pathogenic mutations correlated to TRPS phenotype have been reported, with most of them being nonsense or frameshift mutations.…”
Section: Discussionmentioning
confidence: 99%